SUSTAINABLE STRATEGIES IN WASTE MANAGEMENT IN NUNUKAN REGENCY - Denny Indrawanto (RADJA PUBLIKA, 2026)
Waste is one of the environmental issues that continues to pose a significant challenge for various regions in Indonesia, including Nunukan Regency. This regency, located in North Kalimantan Province, has unique geographical and demographic characteristics, with an area of 14,493 km² and a continuously growing population. This creates significant pressure in managing the waste generated from domestic, industrial, and commercial activities. The waste problem not only impacts the environment but also public health and the sustainability of regional development. Therefore, an effective and sustainable waste management system has become an urgent need to be implemented in Nunukan Regency. This research aims to understand the actual conditions of waste management, identify the factors affecting the effectiveness of waste management, and formulate strategies to improve infrastructure and community participation in waste management. The research method used is descriptive qualitative, with primary data obtained through in-depth interviews, observations, and focus group discussions, as well as secondary data from official documents. The research results show that Nunukan Regency still faces various challenges, such as limited infrastructure, low public awareness, and high volumes of plastic waste. To address this, a holistic approach involving the government, the community, and the private sector is needed, as well as the use of environmentally friendly technology and educational programs to raise public awareness. Thus, it is hoped that the waste management system in Nunukan Regency can become more effective and sustainable.